Explaining The Interplay Between The Inappropriate Use Of Cohesive Ties And Disruption In Text Coherence: A Study In English As A Second Language - Dr. Misbah Afsheen Khan , Misbah Rosheen Khan , Zarsheen Khan Mughal (Migration Letters, 2024)
This study has examined the challenges Pakistani students face as ESL learners while writing coherent academic texts, such as theses and dissertations. Since, it aimed to explore how the incorrect use of cohesive ties (e.g., overusing, underusing, or misusing transitional words and phrases) affects the clarity and logical flow of their writing, the study undertook a sequential mixed method design by combining descriptive text analysis and regression analysis to explain the interplay between text cohesion and coherence. A corpus of twenty initial drafts of theses produced by Social Sciences student writers was collected and descriptively analyzed. The manual descriptive analysis paved the way to conduct regression analysis. The results testified to the causal hypothesis and answered the research questions set in the study. The findings highlight the importance of balanced cohesion in achieving text coherence and suggest that ESL instruction should explicitly teach cohesive ties with special emphasis on lexical cohesion, vocabulary expansion, and self-assessment and editing skills to improve writing quality. The study also reveals a strong connection between cohesion and coherence in ESL writing, contradicting previous assumptions that they are independent constructs.